How Do Local-Level Legal Institutions Promote Development? - Gauri, Varun (2012)
This paper develops a framework and some hypotheses regarding the impact of local-level, informal legal institutions on three economic outcomes: aggregate growth, inequality, and human capabilities. It presents a set of stylized differences between formal and informal legal justice systems, identifies the pathways through which formal systems promote economic outcomes, reflects on what the stylized differences mean for the potential impact of informal legal institutions on economic outcomes, and looks at extant case studies to examine the plausibility of the arguments presented. The paper concludes that local-level, informal legal institutions can support social substitutes for the enforcement of contracts, although these substitutes tend to be limited in range and scale; they are flexible and could conceivably be adapted to serve the interests of the poor and marginalized if supportive organizational and social resources could be brought to support the legal claims of the disempowered; and they are more likely to support personal integrity rights than the positive liberties that are also constitutive of development as freedom.